Kesetaraan Kedudukan Perempuan dan Laki-laki dalam Perspektif Hadis - Mitamimah, Aih (Jurnal Riset Agama, 2021)
This study aims to discuss women and their position from the perspective of hadith. This research method uses a qualitative type through literature study and content analysis. The results and discussion of this study include general views on the position of women, hadith about women, and the position of women from the perspective of hadith. This study concludes that women and their position from the perspective of hadith show that there is equality between women and men, free to share, complement and need each other between women and men, where no distinction will be made between them.